In vivo differentiation of mouse embryonic stem cells into hepatocytes - Choi, DH; Oh, HJ; Chang, UJ; Koo, SK; Jiang, JX; Hwang, SY; Lee, JD; Yeoh, GC; Shin, Hee Sup; Lee, JS; Oh, B (Cognizant Communication Corp., 2002)
Embryonic stem (ES) cells have been regarded as a powerful resource for cell replacement therapy. In recent reports mouse ES cells have been successfully applied in the treatment of spinal cord injury, hereditary myelin disorder of the central nervous system, and diabetes mellitus. Another type of disease that could benefit from the availability of stem cell therapy is liver disease. However, for this potential to be realized, it is necessary to demonstrate the differentiation of ES cells into hepatocytes. To demonstrate the in vivo differentiation potential of mouse ES cells, we injected ES cells into the spleen of immunosuppressed nude mice. Histological analysis of teratomas derived from injected ES cells revealed that some areas contained typical hepatocytes arranged in a sinusoidal structure. The hepatic nature of these cells was further confirmed by showing that transcripts of liver-specific genes were present in the differentiated teratoma using reverse transcriptase-poly me rase chain reaction and immunohistochemistry using several liver-specific antibodies including HEP-PAR, phenylalanine hydroxylase, and mouse N-system aminotransferase to identify the respective proteins in the differentiated hepatocytes. This is the first demonstration that mouse ES cells can differentiate in vivo into a mixed population of hepatocytes of varying maturity. This finding extends the potential use of ES cells in the cell replacement therapy by including its possible application for treating liver diseases.